Changes in cardiopulmonary exercise capacity and limitations 3–12 months after COVID-19. Issue 2 (2nd February 2023) - Ingul, Charlotte Björk; Edvardsen, Anne; Follestad, Turid; Trebinjac, Divna; Ankerstjerne, Odd Andre Wathne; Brønstad, Eivind; Rasch-Halvorsen, Øystein; Aarli, Bernt; Dalen, Håvard; Nes, Bjarne Martens; Lerum, Tøri Vigeland; Einvik, Gunnar; et al.
Rationale: To describe cardiopulmonary function during exercise 12 months after hospital discharge for coronavirus disease 2019 (COVID-19), assess the change from 3 to 12 months, and compare the results with matched controls without COVID-19. Methods: In this prospective, longitudinal, multicentre cohort study, hospitalised COVID-19 patients were examined using a cardiopulmonary exercise test (CPET) 3 and 12 months after discharge. At 3 months, 180 performed a successful CPET, and 177 did so at 12 months (mean age 59.3 years, 85 females). The COVID-19 patients were compared with controls without COVID-19 matched for age, sex, body mass index and comorbidity. Main outcome was peak oxygen uptake ( V ′O2  peak ). Results: Exercise intolerance ( V ′O2  peak <80% predicted) was observed in 23% of patients at 12 months, related to circulatory (28%), ventilatory (17%) and other limitations including deconditioning and dysfunctional breathing (55%). Estimated mean difference between 3 and 12 months showed significant increases in V ′O2  peak % pred (5.0 percentage points (pp), 95% CI 3.1–6.9 pp; p<0.001), V ′O2  peak ·kg −1 % pred (3.4 pp, 95% CI 1.6–5.1 pp; p<0.001) and oxygen pulse % pred (4.6 pp, 95% CI 2.5–6.8 pp; p<0.001). V ′O2  peak was 2440 mL·min −1 in COVID-19 patients compared to 2972 mL·min −1 in matched controls. Conclusions: 1 year after hospital discharge for COVID-19, the majority (77%), had normal exercise capacity. Only every fourth had exercise intolerance and in these circulatory limiting factors were more common than ventilator factors. Deconditioning was common. V ′O2  peak and oxygen pulse improved significantly from 3 months. Exercise capacity improves in COVID-19 patients from 3 to 12 months after hospitalisation, and the majority have normal exercise capacity (77%). Circulatory limitations are more common than ventilatory limitation after COVID-19. Deconditioning is common. https://bit.ly/3DlPxcG